Climate adaptation in the Mediterranean: Where are we? - Guida, Carmen (TeMA - Journal of Land Use, Mobility and Environment, 2022)
Starting from the relationship between urban planning and mobility management, TeMA has gradually expanded the view of the covered topics, always remaining in the groove of rigorous scientific in-depth analysis. This section of the Journal, Review Notes, is the expression of a continuous updating of emerging topics concerning relationships between urban planning, mobility and environment, through a collection of short scientific papers written by young researchers. The Review Notes are made of four parts. Each section examines a specific aspect of the broader information storage within the main interests of TeMA Journal. In particular, the Urban planning literature review section aims at presenting recent books and journals, within global scientific panorama, on selected topics and issues. This contribution aims at defining the definition and intervention domain of ecological transition. The outbreak of a novel coronavirus and consequent health, economic and social crisis is leading to a new era: significant financial resources, plenty room for economic manoeuvres may turn the ongoing pandemic into an opportunity, for the next years, to build more sustainable societies and environments. Within this scenario, urban areas play an essential role, as proved in the second paragraph with the support of interesting scientific publications, which are reviewed in the contribution.